1993
DOI: 10.1111/j.1471-4159.1993.tb03275.x
|View full text |Cite
|
Sign up to set email alerts
|

The Protooncogene bcl‐2 Inhibits Apoptosis in PC12 Cells

Abstract: During development, many neuronal populations undergo a process of normal, programmed cell death, or apoptosis. Trophic factors regulate this process, but the mechanism by which they suppress apoptosis remains unclear. In the immune system, recent studies have implicated the protooncogene bcl-2 in the lymphocyte survival response to growth factors. To determine whether a similar survival pathway exists in a neuroendocrine cell type, we have expressed bcl-2 in the rat pheochromocytoma PC12 cell line and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(117 citation statements)
references
References 16 publications
5
111
0
1
Order By: Relevance
“…In vitro evidence that this gene could be involved in neuronal apoptosis comes from overexpression of this gene in neurons deprived of trophic factors (Garcia et al, 1992;Allsopp et al, 1993;Mah et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro evidence that this gene could be involved in neuronal apoptosis comes from overexpression of this gene in neurons deprived of trophic factors (Garcia et al, 1992;Allsopp et al, 1993;Mah et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Culture of GT1-7 cells (puro and bcl-2 transfected) GT1-7 cells, a hypothalamic neuron cell-derived line (GT1-7puro cells) 28 and bcl-2 transfected cells (GT1-7bcl-2 cells), as previously verified by Mah et al 17 or Kane et al, 29 were maintained in DMEM containing 25 mM D-glucose, supplemented with 10% heat-inactivated fetal bovine serum, 100 U/ml penicillin and 100 mg/ml streptomycin on poly-L-lysine coated plates, in an atmosphere of 5% CO 2 /95% air, at 378C. The medium was changed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…9 ± 11 The cell death repressor protein Bcl-2 inhibits cellular free radical formation 12 ± 14 and cyt c release, 15 blocks the activation of caspases 16 and inhibits apoptosis. 17 Bcl-2 increases the capacity of mitochondria to accumulate Ca 2+ 18 and shifts the redox potential of cells towards reduction. 19 Vander Heiden et al 6 have reported that Bclx(L)-expressing cells adapt to STS treatment by maintaining a decreased DC M , while Shimizu et al 20 have suggested that Bcl-2 over-expression decreases the effectiveness of protonophores in depolarizing the mitochondria by enhancing ion flux.…”
Section: Introductionmentioning
confidence: 99%
“…1) was used in conjunction with immunocytochemical methods. Since PC12 cells are a neuroendocrine linederived originally from a rat adrenal phaeochromocytoma-which do not basally express Bcl-2 [10,15,16], they represent an ideal model in which to examine the putative effects of exogenously expressed Bcl-2 on neuroendocrine peptide expression. Moreover, the use of immunohistochemical methods in the present study facilitated the semi-quantitative determination of marker expression, some of which would have proven difficult to detect by immunoblotting due to their low molecular weight.…”
Section: Resultsmentioning
confidence: 99%
“…In view of these findings it would appear that the reported expression of Bcl-2 in neuroendocrine cells [5][6][7][8] relates either to the well-documented anti-apoptotic actions of this oncoprotein or to additional, as yet undiscovered, functions. Previous studies have shown that forced Bcl-2 expression suppresses apoptosis of PC12 cells [15,16] and it has been speculated that the observed expression of Bcl-2 in oxyntic endocrine cells may promote cytosurvival during their maturation and downward migration from isthmal/neck-localised stem cells [8]. Numerous studies have documented Bcl-2 expression in neuroendocrine tumours such as phaeochromocytomas [18], thymic neuroendocrine tumours [19], and gastroenteropancreatic neuroendocrine tumours [20].…”
Section: Resultsmentioning
confidence: 99%